2021
DOI: 10.3390/molecules26247682
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Mechanical Characterization of Licorice Root and Palm Leaf Waste Incorporated into Poly(urethane-acrylate) (PUA)

Abstract: A poly(urethane-acrylate) polymer (PUA) was synthesized, and a sufficiently high molecular weight starting from urethane-acrylate oligomer (UAO) was obtained. PUA was then loaded with two types of powdered ligno-cellulosic waste, namely from licorice root and palm leaf, in amounts of 1, 5 and 10%, and the obtained composites were chemically and mechanically characterized. FTIR analysis of final PUA synthesized used for the composite production confirmed the new bonds formed during the polymerization process. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Catalyst screening and synthesis of NCO-terminated urethane prepolymer. Following our previous studies on the development of efficient and sustainable lactic acid polymerization [4], and synthesis of biomass-based PUA composite [5] we disclose a low-impact procedure for the synthesis of poly(urethane-acrylate). Several cerium-based catalysts were tested for the urethane oligomer (3a) formation (Table 1), starting from polyethylene glycol (PEG 400, 1a) and isophorone diisocyanate (IPDI, 2a).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Catalyst screening and synthesis of NCO-terminated urethane prepolymer. Following our previous studies on the development of efficient and sustainable lactic acid polymerization [4], and synthesis of biomass-based PUA composite [5] we disclose a low-impact procedure for the synthesis of poly(urethane-acrylate). Several cerium-based catalysts were tested for the urethane oligomer (3a) formation (Table 1), starting from polyethylene glycol (PEG 400, 1a) and isophorone diisocyanate (IPDI, 2a).…”
Section: Resultsmentioning
confidence: 99%
“…TGA analysis of UV-cured films show two weight losses (Fig. 6) [5]. The first decomposition step occurs in the temperature range of 120 • C-350 • C and it is due to the thermal degradation of the hard segments, which involves the breakage of urethane linkage.…”
Section: Synthesis Of Bio-based Poly(urethane-acrylates)mentioning
confidence: 99%
See 1 more Smart Citation
“…The structure of the nucleating agent APAl-12C is tested by FT-IR spectra in Figure 3a. The stretching vibration peaks of -CH 2 -and C=O are detected at about 2917 cm −1 and 1590 cm −1 , which are attributed to the characteristic peaks of lauroyloxy [25]. Moreover, a strong peak at approximately 1476 cm −1 could be assigned to the benzene ring stretching vibration [26].…”
Section: Characterization Of the Nucleating Agent Apal-12cmentioning
confidence: 93%
“…In particular, holm oak has been considered as an alternative source for the production of cellulose pulp [ 11 ], willow flour has been proposed as filler for polyethylene matrix [ 12 ] and poly(lactic acid) into microcellular foam [ 13 ]. On the two remaining fillers, licorice root and palm oil waste, a study concerning their characterization before and after introduction in a limited amount into a poly(urethane-acrylate) (PUA) matrix has been carried out [ 14 ]. It is suggested that for all of the fillers considered, working with MAPP would enable their use as the matrix reinforcement in significant amounts, thus providing scope for further application.…”
Section: Introductionmentioning
confidence: 99%